Pengaruh Product Placement Terhadap Brand Awareness “Fullo” Pada Film “Mencuri Raden Saleh” di Kalangan Remaja - Nurhasanah, Alma Agustina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The times have made many new media more effective and efficient for promoting advertisements. Product placement is now a proven strategy that has been widely used by marketers. Product marketing through product placement is also able to overcome the tendency of audience saturation and the ineffectiveness of advertising on television media, because product placement carries out promotional activities by simply placing products as elements or properties in movies. In addition, product placement in movie plots can also increase brand awareness by the audience). The researcher intends to investigate the impact of product placement on the brand awareness of "Fullo" among adolescents in the film Mencuri Raden Saleh, as indicated by the aforementioned description. The data collection technique employed in this study was the distribution of questionnaires to 100 respondents using a Likert scale. A purposive sampling technique was employed in this investigation. The findings of this investigation suggest that the brand awareness variable (Y) is significantly influenced by the product placement variable (X). The hypothesis test yielded a significance value of 0.000, which is less than the 0.05 threshold. Additionally, the Fcount of 124.269 is greater than the Ftable of 2.701. Therefore, the null hypothesis (H0) is refuted and the alternative hypothesis (H1) is accepted, suggesting that the outcome of this investigation is that product placement has a substantial impact on Fullo's brand recognition in the film Mencuri Raden Saleh.